Development of Sound Wave Resonance Props for Understanding the Phenomenon of Stationary Waves Using an ISLE-Based STEM Approach Model in Supporting Transformation Education - Irwandi Irwandi; Rini Safitri; Mirza Mirza (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop ISLE-based STEM learning media and utilize standing wave resonance tube teaching aids to study the phenomenon of stationary (standing) waves. The method used is research and development (R&D) with the ADDIE development model (Analysis, Design, Develop, Implement, and Evaluate). The results obtained from this study are learning media in the form of Practical Teaching Aids (APP), wave simulation programs and student worksheets for traveling wave and stationary wave experiments. The two learning media have gone through the validation process of material experts and media experts and have been declared suitable for use/implementation by students. The developed APP makes it easy for students to visualize stationary waves in a tube. Student worksheets which is prepared using the ISLE-based STEM model approach, is used as a guide in achieving learning objectives by building students' thinking concepts about stationary wave material through resonance tube experiments. The use of APP provides a visualization display of experimental results so that it helps students understand the concept behind physics processes that are invisible like standing waves